Students Response to Hybrid Learning in Higher Education - Andy Endra Krisna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Hybrid learning has emerged as a significant strategy in higher education, combining face-to-face learning with technology. Theoretical discussions on hybrid learning involve an understanding of contemporary learning concepts, such as constructivism, active learning, and humanistic approaches. The integration of technology in the learning process is seen as a key element for creating a holistic and student-centered learning experience. Instructional design principles, motivation theories, and understanding online learning concepts are also important in understanding the dynamics of hybrid learning. This research was conducted using a qualitative descriptive approach which purpose is to analyze students’ response to hybrid learning in higher education. The students in this research are the first semester students at Widya Karya Catholic University who are taking an English subject. Hopefully that this research gives a significant contribution to the development of pedagogical thinking and the practical application of hybrid learning in higher education institutions.